Effects of Leontice leontopetalum and Bongardia chrysogonum on oxidative stress and neuroprotection in PTZ kindling epilepsy in rats - Ergul Erkec, Ozlem; Arihan, Okan; Kara, Mehmet; Karatas, Ersin; Erten, Remzi; Demir, Halit; Meral, Ismail; Mukemre, Muzaffer; Ozgokce, Fevzi (Cellular and Molecular Biology, 2018)
We investigated the effects of Leontice leontopetalum and Bongardia chrysogonum on apoptosis, gamma-aminobutyric acid (GABAA) receptor positive cell number, cyclin-B1 and bcl-2 levels and oxidative stress in pentylenetetrazol (PTZ) kindling in rats. Kindling was produced by subconvulsant doses of PTZ treatments in rats. Wistar albino rats were divided into 4 groups; Control, PTZ treated (PTZ), PTZ+L. leontopetalum extract treated (PTZ+LLE) and PTZ+B. chrysogonum extract treated (PTZ+BCE) groups. Extracts were given a dose (200 mg/kg) 2h before each PTZ injection. PTZ treatment significantly decreased the glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) activities and bcl-2 levels and increased the total oxidant status (TOS), malondialdehyde (MDA), cyclin B1, oxidative stress index (OSI) and number of neurons that expressed GABAA receptors when compared to the control. LLE and BCE possessed antioxidant activity in the brain and ameliorated PTZ induced oxidative stress, decreased cyclin-B1, increased bcl-2 levels, and kept the GABAA receptor number similar to that of the control despite the PTZ application.